Role of Social Media in Facilitating Financial Scams in Abuja, Nigeria: Development Communication Interventions for Prevention - Adebayo, Mayowa Adebayo (African Journal of Stability and Development (AJSD), 2025)
This study explored the critical role of social media in facilitating financial scams in Abuja, addressing the urgent need for effective preventive strategies. The increasing prevalence of scams, including phishing, fake investment opportunities, and fraudulent online stores, poses significant financial risks to residents. Grounded in Social Learning Theory and the Diffusion of Innovation Theory, the research aimed to understand the behaviours associated with online scams and identify communication strategies for mitigating their impact. Employing a quantitative research design, the study gathered data from a sample of 390 respondents, selected through purposive sampling to ensure representation of social media users, scam victims, and digital marketing professionals. Surveys served as the primary instrument for data collection, enabling the assessment of awareness regarding scam tactics and residents' experiences with fraud. The findings revealed a significant lack of awareness and preparedness among the community, highlighting gaps in understanding common scams and prevention strategies. Based on these insights, several recommendations were proposed. Workshops and seminars were suggested to educate residents about the tactics employed by scammers, alongside targeted communication campaigns leveraging mass media and social media influencers to raise awareness. Additionally, establishing a framework for evaluating existing scam prevention strategies was deemed essential for continuous improvement. Innovative interventions, such as mobile applications for reporting scams and online forums for community support, were recommended to support scam reporting and community awareness, thereby enhancing digital literacy. Finally, fostering partnerships among government agencies, tech companies, and community organisations emerged as a crucial solution for developing comprehensive strategies to combat financial scams effectively.